The adoption of pottery on Kodiak Island: Insights from organic residue analysis. (20th July 2020) - Admiraal, Marjolein; Lucquin, Alexandre; von Tersch, Matthew; Craig, Oliver E.; Jordan, Peter D.
Abstract: Pottery technology, originating in Northeast Asia, appeared in Alaska some 2800 years ago. It spread swiftly along Alaska's coastline but was not adopted on Kodiak Island until around 500 cal BP, as part of the Koniag tradition. While in the southeast pottery was used extensively, people on the northern half of the island did not adopt the technology. What drove these patterns of adoption and non-adoption on Kodiak Island? To better understand the role of ceramic technology in the Koniag tradition we used organic residue analysis to investigate pottery function. Results indicate that pottery was used to process aquatic resources, including anadromous fish, but especially marine species. Based on archaeological and ethnographic data, and spatial analysis of pottery distributions and function, we hypothesize that Koniag pottery was a tool inherent to the rendering of whale oil on the southeast coast of Kodiak Island, supporting previous suggestions by Knecht (1995) and Fitzhugh (2001). When viewed in the broader historical context of major technological and social transformations, we conclude that social identity and cultural boundaries may also have played a role in the delayed and partial adoption of pottery on Kodiak Island.